Transformation of the Second Floor Function of Kosambi Market into a Communal Space Based on Visitor Perceptions - Sumiati, Melina (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
Traditional markets are one of the key economic sectors in both urban and rural areas, serving as venues for various activities. Numerous efforts and policies have been implemented to transform traditional markets into not only economic centers but also spaces for social and cultural interaction. Over time, certain parts of these market spaces have undergone changes influenced by various factors, including economic development. The spatial transformation on the second floor of Pasar Kosambi has triggered diverse perceptions among individuals and community groups who visit the area. These perceptions play an essential role in how people understand and respond to their surrounding environment. This study aims to identify the causes of spatial transformation and to analyze how the second floor of Pasar Kosambi has evolved into a communal space, as well as to understand visitors’ perceptions of this space. The research adopts a qualitative descriptive approach, with data collected through literature review, observation, documentation, and questionnaires. A total of 37 respondents participated in the questionnaire survey. Visitor perception of the communal space on the second floor of Pasar Kosambi is measured across three aspects: (1) the cognitive aspect, which includes 5 categories (comfort, cleanliness, quality, design, and accessibility) with a total score of 99.52%; (2) the affective aspect, comprising two categories (emotions and the sleepy-lively scale) with a total score of 86.4%; and (3) the conative aspect, which involves future behavioral intentions, scoring 76.7%. The overall perception score reached 262.62%, indicating a strong agreement across all aspects. The findings illustrate how the functional transformation of the second floor of Pasar Kosambi into a communal space centered on specific commodities is perceived by visitors in terms of their needs, experiences, and interactions within the space.